Are Vitamin E Supplementation Beneficial for Female Gynaecology Health and Diseases? - Nur Amira Md Amin; Siti Hamimah Sheikh Abdul Kadir; Akmal Hisyam Arshad; Norhaslinda Abdul Aziz; Nurul Alimah Abdul Nasir; Normala Ab Latip (Molecules, 2022)
Vitamin E is known as an essential vitamin, and many studies had demonstrated the importance of vitamin E throughout the reproductive process, such as miscarriage, premature birth, preeclampsia, and intrauterine growth restriction, which could be caused by a lack of vitamin E during pregnancy. Its potent antioxidant properties can counteract the oxidative stress induced by oxygen free radicals and imbalance of oxidative-antioxidant levels, hence it may play a role in maintaining the normal function of the female reproductive system. Despite the fact that vitamin E is acknowledged as the substance needed for reproduction, its beneficial effects on female fertility, gynaecological health, and diseases are still poorly understood and lacking. Therefore, the goal of this paper is to provide a summary of the known roles of vitamin E supplementation in women for gynaecological health and reproductive-related diseases, as well as its future perspective.